Postnatal predictors for outcome in congenital diaphragmatic hernia: A singlecenter retrospective cohort study from India - Chandrasekaran, Ashok; Rathnavelu, Ezhilarasan; Mulage, Lingaraja; Ninan, Binu; Balakrishnan, Umamaheswari; Amboiram, Prakash; Shaik, Shafi Jan Mohammad; Ramaswamy, Sarvanan (Indian Journal of Child Health, 2016)
Background: Congenital diaphragmatic hernia (CDH) has high morbidity and mortality. Many outcome predictors have been tried. Objective: To assess the short-term outcomes of neonates with isolated CDH and find the predictors of outcome. Methods: Neonates with isolated CDH managed over 12-year period from June 2004 were analyzed. Antenatal counseling, delayed surgery after stabilization, primary conventional ventilation and rescue high frequency ventilation if needed is the unit protocol. Details on baseline characteristics, delivery room management, clinical details, ventilation details, management of pulmonary hypertension, inhaled nitric oxide usage, operative details, and post-operative period were noted. Oxygenation index (OI) was calculated, and echocardiography findings on pulmonary hypertension were noted. Outcome predictors were assessed. Results: 40 neonates with isolated CDH were managed during the study period. The mean birth weight and gestation were 37.7±1.55 weeks and 2830±480 g, respectively. The majority of them were intramural and had an antenatal diagnosis. Definitive sepsis, pneumothorax, and severe pulmonary hypertension were seen in 10, 9, and 17 neonates, respectively. In 32 neonates, surgical repair was done and 31 (78%) survived at discharge. Median (range) of maximum OI on day 1 was 6 (2.2-39) and 59.9 (7.65-96) for survivors and non-survivors,respectively. Area under the curve (AUC) for OI prediction of survival was 0.94 (confidence interval 0.86-0.99). The adjusted odds ratio for survival, when maximum OI was below 15, was 36.2 (4.6-142). Receiver operating curve showed AUC for OI in predicting survival was 0.95 (0.86-0.99). Conclusion: We found 78% survival for isolated CDH neonates using standard protocol and OI is a good predictor for survival.